The girl who chased the moon [compact disc, unabridged] : a novel - Allen, Sarah Addison (Books on Tape/Random House, 2009)
Emily Benedict came to Mullaby, North Carolina, hoping to solve at least some of the riddles surrounding her mother's life. Such as, why did Dulcie Shelby leave her hometown so suddenly? And why did she vow never to return? But the moment Emily enters the house where her mother grew up and meets the grandfather she never knew, a reclusive, real-life gentle giant, she realizes that mysteries aren't solved in Mullaby, they're a way of life. Here are rooms where the wallpaper changes to suit your mood. Unexplained lights skip across the yard at midnight. And a neighbor bakes hope in the form of cakes.